Gender differences in spontaneous coronary artery dissection: a nationwide analysis. (25th November 2020) - Krittanawong, C; Narasimhan, B; Hassan Virk, H; Yue, B; Herzog, E
Abstract: Background: Spontaneous coronary artery dissection (SCAD) is a very rare cause of acute coronary syndromes in young otherwise healthy patients with a striking predilection for the female gender. Unfortunately, SCAD can result in significant morbidities and mortality. The pathological mechanism has not been fully clarified yet but hormonal changes might represent a sufficiently convincing explanation for some patients with SCAD. We hypothesized that gender difference in mortality in SCAD patients. Methods: Data for this retrospective cohort study were extracted from the Nationwide Inpatient Sample for 2014 using the 9th revision of the International Classification of Diseases (ICD) 414.12 (spontaneous coronary artery dissection). Demographics, in-hospital mortality, conventional risk factors (diabetes, hypertension, hyperlipidemia, alcohol and tobacco abuse), acute critical illnesses like sepsis, septic shock, stroke, acute respiratory insufficiency, acute renal failure, and chronic conditions (anxiety, depression, malignancy and metastatic diseases) were studied. Univariate and multivariate logistic regression modeling were performed to determine predictors associated with the development of inpatient mortality in SCAD patients. All analyses were conducted using R 3.4.0 and STATA/MP 14.2. All p-values were two-sided, and statistical significance was determined at the level of p<0.05. Result: A total of 270 SCAD patients were identified. Of those SCAD patients, no fibromuscular dysplasia (FMD) or pregnancy were identified. Patients were predominantly women (71%) and the mean age was 53 years. Overall in-hospital mortality was 5.6%, with 6.6% in male and 5.3% in female. Ethnicity, gender, stroke, acute renal failure, anxiety and depression did not predict mortality, length of stay, annual income, total hospital charge (all p>0.05). Multivariate analysis revealed no gender difference in SCAD patients and no independent predictors of mortality were identified. Conclusions: This large nationwide study reveals that SCAD may be underdiagnosed but underutilization of work up such as FMD. SCAD is thought to be hormone related likely associated with female gender. Our results showed that no gender difference in mortality. Further large prospective studies are needed to determine gender difference in mortality and other predictors in mortality. Funding Acknowledgement: Type of funding source: None